An investigation of Generation Y travellers' beliefs and attitudes towards green hotel practices: a view from active and passive green Generation Y travellers. Issue 2 (3rd April 2017) - Huh, Chang; Chang, Howook "Sean"
Abstract: Generation Y, also known as Millennial, have a reputation for being more environmentally conscious than the Baby Boomers and Generation Xers who preceded them. However, the literature on hospitality and tourism has not discussed Generation Y's changing beliefs and attitudes towards sustainability and encompassing their points of view about lodging green operations, even though millennial travellers will be a dominant customer segment in the hotel industry for the next 20 years. This study identified heterogeneous groups among members of Generation Yers who hold similar beliefs and attitudes towards the environment and examined the green hotel practices they seek when travelling. A questionnaire survey was developed and administered in New York, Florida and Michigan. Using 318 samples, this study categorized millennial green travellers as active or passive, based on their beliefs and attitudes towards green initiatives. The results indicated that to Generation Y travellers in general, green hotels should have recycling and disposal programmes. t -Test results also exhibit significant differences in the green hotel practice factors expected by active and passive green millennial travellers. To active green travellers, green certification and visible green advertisement are important factors when they stay in a green hotel. The implications of the study are discussed.